Exploring The Impact of Self-Regulated Learning on Reducing Students' Mathematics Anxiety - harahap, Lidra Ety Syahfitri; Sri Andayani; Ekwan, Deflimai (Program Studi Tadris Matematika Universitas Islam Negeri (UIN) Salatiga, 2024)
The study of mathematics often presents challenges due to anxiety, which can adversely affect students' understanding and performance. Research on self-regulated learning has received increasing attention as a strategy to address this issue. This article presents a comprehensive literature review to explore the relationship between self-regulated learning and anxiety in mathematics. Using the PRISMA procedure, 28 studies were selected from 2018 to 2024 to explore the relationship between self-regulated learning and math anxiety grouped by level of research, methodology, sample, and instruments used. The review showed that stronger levels of self-regulated learning were associated with lower levels of math anxiety, while lower levels of self-regulated learning were associated with higher math anxiety. These findings provide valuable insights for educators and researchers in developing strategies to increase self-regulated learning and reduce students' math-related anxiety. Understanding these relationships makes it possible to design more targeted interventions to improve teaching practices as well as student learning outcomes in mathematics.